#TITLE_ALTERNATIVE# - DANANJAYA (NIM 13302023), ALEX
Automation systems have significant role in production process. Production process will become more economic with presence of apropriate automation systems. Formal methods can be used to improve performances of an automation system . One of formal methods that is known to design automation systems is Signal Interpreted Petri Nets (SIPN). The difference between ordinary Petri Nets and SIPN is the ability of SIPN to describe the interaction between control algorithm and its environment. The interaction is described by input and output signals. Since the interaction can be described, SIPN diagram can be implemented in control devices like Programmable Logic Controllers (PLCs). In this final project, SIPN is used to design PLC-based automation system to be applied in bioethanol production. Bioethanol fuel is one of alternative energy that can be used to replace fossil fuel. Since bioethanol fuel has promising potentials, there will be increasing demand on bioethanol in the future. In order to meet this demand, some researches to obtain economic production process is needed. One of the research is to implement automation system. A reliable bioethanol automation system can be achieved by using SIPN method. The SIPN diagram will be implemented on PLCs programming in ladder logic diagram. SIPN diagram is analyzed by using invariant analysis and transparency metrics. Positive P–invariant, T–invariant, are obtained from the invariant analysis and, transparency metrics = 0,98.